Influence of Biochar Feedstocks on Nitrate Adsorption Capacity - Riad Eissa; Lordwin Jeyakumar; David B. McKenzie; Jianghua Wu (Earth)
The demand for intensive agriculture to boost food and crop production has increased. High nitrogen (N) fertilizer use is crucial for increasing agricultural productivity but often leads to significant nitrate losses, posing risks to surface and groundwater quality. This study examines the role of biochar as a soil amendment to enhance nutrient retention and mitigate nitrate leaching. By improving nitrogen efficiency, biochar offers a sustainable strategy to reduce the environmental impacts of intensive agriculture while maintaining soil fertility. An incubation study investigated four biochar feedstocks: spruce bark biochar at 550 °C (SB550), hardwood biochar (75% sugar maple) at 500 °C (HW500), sawdust (fir/spruce) biochar at 427 °C (FS427), and softwood biochar at 500 °C (SW500), to identify the most effective nitrate adsorbent. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR) were employed to analyze biochar morphology and surface functional groups. Adsorption isotherms were modeled using the Langmuir and Freundlich equations. The results indicated that surface functional groups, such as aromatic C=C stretching and bending, aromatic C–H bending, and phenolic O–H bending, play crucial roles in enhancing electrostatic attraction and, consequently, the nitrate adsorption capacity of biochar. The equilibrium adsorption data from this study fit well with both the Langmuir and Freundlich isotherm models. Among the four biochar types tested, SB550 exhibited the highest nitrate adsorption capacity, with a maximum of 184 mg/g. The adsorption data showed excellent conformity to the Langmuir and Freundlich models, with correlation coefficients (R2) exceeding 0.987 for all biochar types. These findings highlight the high accuracy of these models in predicting nitrate adsorption capacities.